Impact of Virtual Clinics on Streamlining NHS Outpatient Waiting Lists and Carbon Emissions - Bhaskar Amarnath Bhavanasi MBBS, MS(Ortho), FEBOT, FRCS Edn(T&O); Shrikant Kulkarni MBBS, MS(Ortho), FRCS(T&O) (Foot & Ankle Orthopaedics)
Background: The National Health Service (NHS) outpatient waiting list is growing, affecting specialties like foot and ankle. Delays are due to increasing demand, limited resources, and administrative inefficiencies. Virtual clinics are being explored to reduce physical clinic burdens and provide timely care. This study investigates the effectiveness of virtual clinics in reducing prolonged waiting times in the foot and ankle specialty. Emissions from personal vehicles are a primary driver of climate change, which is a little recognized benefit of virtual clinics. Methods: We analyzed outcomes from a virtual elective foot and ankle clinic, overseen by a specialist consultant, for new elective referrals over 4 months. Data for 175 patients were collected from Lorenzo, our electronic health records system. We also assessed the success rate of virtual consultations in terms of accurate diagnoses and effective treatment plans. Measured distance to the hospital based was on patients’ residential address. Results: The virtual clinic effectively managed patients. Of the 175 patients, 48.6% completed treatment, and were discharged, and 53.7% were managed without face-to-face consultations. In addition, 66.3% did not need in-person visits; this includes patients treated and discharged and who were referred for investigations. In this clinic, avoiding 1 visit to the hospital by 116 patients saved travel of 1040 miles. Conclusion: The widespread adoption of virtual clinics can provide a convenient and cost-effective health care solution for patients and also potentially help reduce carbon emissions contributing to control global warming. Level of Evidence: Level IV, retrospective case series.